Penggunaan Imunostik sebagai Uji Serologi untuk Deteksi Brucella abortus pada Sapi (APPLICATION IMMUNOSTICK ASSAY FOR SEROLOGICAL TEST BRUCELLA ABORTUS IN BOVINE) - Astarina, Dhevie Kenny; Pribadi, Eko Sugeng; Pasaribu, Fachriyan Hasmi (Jurnal Veteriner; Vol 19 No 2 (2018), 2018)
Serological test is one of diagnostic method to detect pathogenicity brucella.  Several methods are being improving such as Rose Bengal Test (RBT), Complement Fixation Test (CFT) dan Enzyme-linked Immunosorbent Assay (ELISA). Immunostick has an accuracy equivalent to ELISA and is easy to apply in the field so it is possible to be applied as a rapid test for brucellosis detection. The study aim was to know sensitivity and specificity of immunostick that were used to detecte antibody Brucella abortus using commercial antigens of B. abortus Strain 19 (S19) and B. abortus Strain 99 (S99). The test have compared with ELISA. The tests were conducted in two stages, namely (i) immunostick ability to detect antibodies in seropositive and seronegative serum, and (ii) the immunostick result were compared with ELISA result in serum grup that were be know and unknown status. A total of 250 serums were examined and result indicated that immunostick can be detect B. abortus antibodies in cattle serum with sensitivity 100%. Immunostick specifity were 45,45% for B. abortus S99(1) antigen; 78,79% for B. abortus S99(2) antigen and 51,52% for B. abortus S19 antigen. When the test compared with ELISA, the sensitivity 82,86% and the spesifity were 52,31% for B. abortus S99(1) antigen; 93,54% and 79,71 for B. abortus S99(2) antigen and 82,86%  and 58,46% for B. abortus S19 antigen.